Modeling the impact of exchange rate fluctuations on agricultural performance: Evidence from Morocco during the period 2000-2023 - Mohamed, ES-SANOUN; ELMOUKHTAR, Mohamed; Mohammed, FILAL; Yassine, NISSAR; Mounir, BENBOUBKER (Edelweiss Applied Science and Technology, 2024)
The agricultural sector is a cornerstone of Morocco's economic development, contributing significantly to food security, employment, raw materials for agro-industries, and national GDP. This study investigates the impact of Real Effective Exchange Rate (REER) fluctuations on agricultural performance in Morocco from 2000 to 2023. Using an econometric framework, three models were developed: the first examines the direct effects of REER on agriculture, the second explores the implications of REER misalignments (calculated via the Behavioral Equilibrium Exchange Rate (BEER) approach), and the third analyzes the distinct impacts of REER overvaluation and undervaluation. The ARDL method was employed to estimate these models, incorporating control variables such as GDP Growth Rate, inflation, and foreign direct investment. The findings reveal that REER fluctuations significantly influence agricultural performance, with undervaluation enhancing export competitiveness and overvaluation diminishing profitability and production. REER misalignments, particularly overvaluation, have adverse long-term effects on the sector’s competitiveness. Conversely, undervaluation fosters growth through export stimulation and increased investments. The study underscores the need for a strategic exchange rate management policy aimed at stabilizing the REER and mitigating misalignments to support sustainable agricultural growth and competitiveness in Morocco. These insights provide a foundation for policymakers to devise macroeconomic strategies that enhance the agricultural sector’s resilience and contribution to national economic development.